Au(111) Surface Oxidation Kinetics Probed by Electrocatalytic Oxidation of Formic Acid. Issue 11 (1st November 2022) - Matzik, Felix M.; Hermann, Johannes M.; Kibler, Ludwig A.; Jacob, Timo
Abstract : The kinetics of surface oxidation for Au(111) in 0.1 M HCOOH + 0.1 M HClO4 was studied at 20 °C utilizing the electrocatalytic formic acid oxidation reaction (FAOR). In the surface oxidation region, cyclic voltammetry shows a distinct dependence of FAOR on scan rate revealing simultaneous deactivation of active surface sites. The surface oxide is essentially inactive for the FAOR. A series of current-time curves was recorded after potential steps into the potential range between 0.65 and 1.00 V vs saturated Mercury-mercurous sulfate electrode and analyzed within a three-step surface oxidation model, which successively involves (i) adsorption at surface defects, (ii) adsorption on well-defined Au(111) terraces, and (iii) two-dimensional nucleation-and-growth on terraces. Although Au surface oxidation is by far more complex, the system can be described in terms of the intrinsic activity of the Au(111) surface j max FAOR E and the oxide coverage θ t, E . The chronoamperometric measurements can be modeled without considering the interaction of the oxide species with the FAOR and the co-adsorption of anions. The potential dependence of the kinetic parameters is used to obtain theoretical current-time curves for FAOR on Au(111). This study sheds light on the "fast FAOR" and contributes to the understanding of degradation phenomena in electrocatalysis.